Herlyn-Werner-Wunderlich Syndrome: A Case Report - Islam, SM Saiful (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Herlyn-Werner-Wunderlich Syndrome (HWWS) is a rare developmental disorder of female urogenital tract consisting of paired uterus, obstructed hemivagina and unilateral renal agenesis. Here, authors described a case of a 10 years old girl with HWWS who presented to pediatric emergency with recurrent lower abdominal pain shortly following menstruation and dysmenorrhea. The diagnosis was confirmed by abdominal MRI. Examination under anesthesia revealed two vaginal opening, of which left is widely open and the right is completely closed with bulging hymen. A hymeneal incision was made with evacuation of the cavity. At present, the preferred surgical option is resection of as completely of the obstructing vaginal septum as possible and marsupialization for patients with completely obstructed hemivagina with blind hemivagina and incompletely obstructed hemivagina. The outcome of patients with HWWS is generally good with early detection of illness and prompt management. They can have normal sexual relations with preserved fertility. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 70-73